UNICEF's lessons learned from the education response to the COVID-19 crisis and reflections on the implications for education policy. (September 2021) - Lennox, Janet; Reuge, Nicolas; Benavides, Francisco
Highlights: COVID-19 opened up education delivery worldwide. Up to one-third of schoolchildren missed out, and learning losses mounted. Careful planning of new options can overcome longstanding barriers. The pandemic can be used to make sector planning and budgeting more resilient. Abstract: COVID-19 triggered mass innovation that grew flexible learning modalities and pathways that can be built upon in future sector plans to make education systems more resilient. These tools must be paired with investments in the people expected to use them and strengthened data systems. To ensure plans are rooted in ever-pressurised budgets, Education Ministers will increasingly need to turn to economic analysis. Expansion of partnerships will be necessary to secure greater and more innovative forms of finance but also affordable digital learning solutions. If these opportunities are seized alongside the disruption wrought by the pandemic, they can equalize opportunities and accelerate progress.